THE RELATIONSHIP OF ORGANIZATION FAILURE MODES AND EFFECTS ANALYSIS WITH THE SAFETY QUALITY FOR SUPPLY CHAIN RISK MANAGEMENT - Hezla, L; Avdotin, V; Derouiche, L; Plushikov, V; Norezzine, A; Kucher, D; Khomenets, N; Poddubsky, A; Gadzhikurbanov, A; Ivanov, N; Dokukin, P; Rebouh, N.Y (International Journal of Supply Chain Management, 2020)
Abstract- Supply chain risk management (SCRM) is a key component of not only supply success but firm success as well. All Companies aim to achieve the highest level in quantity and quality of their products in the shortest time while preserving the safety of their workers and providing all appropriate conditions for them. Whereas many institutions spend a lot of money to implement international safety and quality standards in order to reach this goal, they continue to suffer from some failures on the level of worker safety and unstable product quality. The presence of the human factor necessarily means the possibility of errors, and these errors naturally have accumulations that may reach even the furthest point in the organization and this leads to an increased possibility of accidents and fluctuations in product quality and waste of time. In view of the common goals and similarities between the Failure Modes and Effects Analysis (FMEA) organization, supply chain risk management, and the effective pivotal role of the FMEA organization in extracting points of failure and errors at the FMEA organization and field levels. Linking them in a way that allows managers to explore errors in the least time possible to remedy its consequences. The relationship between the FMEA organization and product quality management aims to improve performance and improve product quality in the shortest possible time.